online advertising
Processing math: 100%

Thursday, December 31, 2015

On repeated roots

Following up with the last post, we wanted to understand why xe2x is the solution when 2 is a repeated root.

Let's start with this, (p(x)eax)(k)

We notice this pattern

(p(x)eax)=eax(ap(x)+p(x))
(p(x)eax)=eax(a2p(x)+2ap(x)+p(x))
(p(x)eax)=eax(a3p(x)+3a2p(x)+3ap(x)+p(x))

Feel like binomial expansion? Let's prove this.

Let S(n) be the statement (p(x)eax)(n)=eaxni=0((ni)aip(ni)(x))

S(0) is obviously true, now let's assume S(k) is true and

(p(x)eax)(k)=eaxki=0((ki)aip(ki)(x))

Now we differentiate both sides once more, we get

(p(x)eax)(k+1)=eax(ki=0((ki)aip(ki)(x)))+aeaxki=0((ki)aip(ki)(x))

Don't be shied away from the first term, it is just differentiating polynomials, so adding 1 to the differentiation times and that's all. grouping terms, we will get

(p(x)eax)(k+1)=eaxki=0((ki)aip(k+1i)(x))+aeaxki=0((ki)aip(ki)(x))=eaxki=0((ki)aip(k+1i)(x))+aeaxk+1i=1((ki1)ai1p(k+1i)(x))=eaxki=0((ki)aip(k+1i)(x))+eaxk+1i=1((ki1)aip(k+1i)(x))=eax(k0)a0p(k+10)(x)+eaxki=1((ki)aip(k+1i)(x))+eaxki=1((ki1)aip(k+1i)(x))+eax(kk+11)ak+1p(k+1(k+1))(x)=eaxa0p(k+1)(x)+eaxki=1((ki)aip(k+1i)(x))+eaxki=1((ki1)aip(k+1i)(x))+eaxak+1p(0)(x)=eaxa0p(k+1)(x)+eaxki=1(((ki)+(ki1))aip(k+1i)(x))+eaxak+1p(0)(x)=eaxa0p(k+1)(x)+eaxki=1((k+1i)aip(k+1i)(x))+eaxak+1p(0)(x)=eaxk+1i=0((k+1i)aip(k+1i)(x))

Well, a little more complicated than I wanted it to be, but I proved the result.

Next, we assume the differential equation has constant coefficient like this nj=0cjy(j)=0, and that r is a root of multiplicity k. In this case, we claim xmerx is a solution for the differential equation for 0m<k. All we need to do is to put it back to the equation and use our result above:

nj=0cjy(j)=nj=0cjerxji=0((ji)rip(ji)(x))=erxnj=0cjji=0((ji)rip(ji)(x))=erxnj=0cjji=0((ji)rjip(i)(x))=erxni=0nj=icj((ji)rjip(i)(x))=erxni=0nj=icj(j!i!(ji)!rjip(i)(x))=erxni=0p(i)(x)i!nj=icj(j!(ji)!rji)

Note that the inner summation is really just the characteristics polynomial differentiated i times evaluated at r, and we know r is a root of multiplicity k, so for all i<k, the term is zero.

For the other terms, we differentiated p(x) at least k times, but p(x)=xm, so the derivative vanishes, and those terms go to 0 as well. Combining the two facts, the differential equation is satisfied, and therefore it is a solution!

Q.E.D.

The magic step of the fourth equal sign probably need some explanation. One can better visualize that if one programs, it is basically a loop transformation

for (j = 0 to n) { for (i = 0 to j } { } }

is transformed to

for (i = 0 to n) { for (j = i to n } { } }

The easiest way to see why this transformation is valid is by generating the (i, j) tuples created by these loops.

No comments:

Post a Comment